2002
DOI: 10.12968/jowc.2002.11.8.26429
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence data: can we ensure greater accuracy?

Abstract: Practitioners in the UK will only know if they are meeting targets on pressure ulcer reduction if they provide valid and reliable prevalence and incidence data. But all too often, published data contain inconsistencies and can be misleading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Nonetheless, prevalence studies are commonly undertaken, and probably their greatest value rests in focussing the attention towards pressure ulcers. In addition, they allow for the assessment of prevention practices and adherence to standards and guidelines (Bethell 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, prevalence studies are commonly undertaken, and probably their greatest value rests in focussing the attention towards pressure ulcers. In addition, they allow for the assessment of prevention practices and adherence to standards and guidelines (Bethell 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review did not identify additional factors about wound descriptions or assessment that might have been omitted by the participants. However, separate studies of documentation (Hon & Jones, 1996; Sterling, 1996; Bethell, 2002), showed that, when left without the framework of a WAF, nurses do not record anything on some potentially clinically significant features. An explanation is that nurses do not work with a variety of wounds everyday, unlike tissue viability specialists, and might need cues.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective design is considered more appropriate, particularly as consistency in data collection is essential 2. Finally, it is important to report the incidence of PUs within the context of risk status of the population of interest, in tandem with the availability and use of preventative strategies 3.…”
Section: Commentarymentioning
confidence: 99%